Synthesis, Characterisation, Computational Studies and Nonlinear Optical Properties of Cu(II), Ni(II) and Co(II) Complexes with 2-Hydroxynaphthaldehyde and 2,4-Dimethylaniline Derived Schiff Base Ligands - Arya, Ved Prakash; Maurya, Alok Kumar; Jaiswal, Nitesh (Asian Journal of Chemistry, 2026)
A series of transition metal complexes derived from 2-hydroxynaphthaldehyde based Schiff base ligand designed and synthesised. The Schiff base ligand 1 was prepared via condensation of 2-hydroxy-1-naphthaldehyde with 2,4-dimethylaniline. The corresponding complexes 2-4 of Cu(II), Ni(II) and Co(II) ions were synthesised using Schiff base ligand in 1:2 molar ratios. The synthesised ligand and its metal(II) complexes were characterised using elemental analysis, UV-Vis, FT-IR, 1H NMR and mass spectrometry. Density functional theory (DFT) calculations at the B3LYP level with a basis set of 6-31G(d,p) were employed to optimize geometries, predict frontier molecular orbitals, compute HOMO–LUMO gaps and analyse electronic distribution. Non-liner optical properties of ligand and metal(II) complexes also computed using DFT method. The combined experimental and theoretical results suggest tetrahedral geometry in complex 2 and square-planar geometry in complexes 3 and 4.